2023
DOI: 10.1039/d3dt00607g
|View full text |Cite
|
Sign up to set email alerts
|

Reactive FLP–alkyne addition products: a route to anionic and zwitterionic phosphines

Abstract: Combination of a phosphinidene precursor, B(C6F5)3 and 4-ethynyltoluene afforded the FLP addition product, Et2N(C14H10)PC(Tol)=CH (B(C6F5)3) 2. Compound 2 reacts with halides, pseudo-halides or Me3SiSPh to provide a facile route to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…On studying the reaction of phosphinidene precursors 102 as the basic components of FLPs, we showed that they react with alkynes to effect the expected FLP addition reaction. However, subsequent addition of phosphine liberated anthracene yielding a phosphino–phosphenium zwitterion (Scheme 37).…”
Section: Stoichiometric Reactivitymentioning
confidence: 99%
“…On studying the reaction of phosphinidene precursors 102 as the basic components of FLPs, we showed that they react with alkynes to effect the expected FLP addition reaction. However, subsequent addition of phosphine liberated anthracene yielding a phosphino–phosphenium zwitterion (Scheme 37).…”
Section: Stoichiometric Reactivitymentioning
confidence: 99%